A Juridical Review of Licensing Regulations and Operational Rules for Drones under Law Number 21 of 2025 Concerning Airspace Management in Indonesia - Gesti Magdalena Sarante (Indonesian Journal Publisher, 2026)
The rapid development of drone technology in Indonesia has generated substantial contributions across multiple sectors, including aerial photography, geospatial mapping, infrastructure inspection, precision agriculture, logistics, and security surveillance. Nevertheless, the existence of fragmented regulatory instruments, such as PM 90/2023 and SE 15/2024, has led to legal uncertainty, increased risks of misuse (e.g., espionage and privacy violations), challenges in law enforcement, and constraints on technological innovation. In response, the enactment of the Airspace Management Law on November 25, 2025, represents a strategic effort to establish a comprehensive regulatory framework. This study aims to examine how licensing and operational provisions within the law ensure flight safety and national security, as well as to evaluate their effectiveness. This research employs a normative juridical method with legislative and conceptual approaches. Data were collected through library research, encompassing primary legal materials (Airspace Management Law, Aviation Law No. 1/2009, and the Chicago Convention), supported by secondary and tertiary sources. The analysis adopts a normative qualitative approach grounded in Rechtsstaat theory, Friedman’s legal system theory, and air law doctrine. The findings demonstrate that preventive licensing mechanisms, including operator registration and authorization, alongside operational regulations such as altitude restrictions, visual line-of-sight (VLOS) requirements, prohibited zones, and sanctions, contribute significantly to minimizing collision risks and preventing unlawful activities, thereby reinforcing airspace sovereignty. However, the effectiveness of these regulations remains constrained by implementation challenges, including procedural complexity, limited public awareness, and insufficient supervisory capacity. Accordingly, strengthening regulatory harmonization, digital-based governance, public education, and technological adaptation is essential to enhance the overall effectiveness of drone regulation in Indonesia.